Systemic DKK1 neutralization enhances human adipose‐derived stem cell mediated bone repair. (30th December 2020) - Negri, Stefano; Wang, Yiyun; Sono, Takashi; Qin, Qizhi; Hsu, Ginny Ching‐Yun; Cherief, Masnsen; Xu, Jiajia; Lee, Seungyong; Tower, Robert J.; Yu, Victoria; Piplani, Abhi; Meyers, Carolyn A.; et al.
Abstract: Progenitor cells from adipose tissue are able to induce bone repair; however, inconsistent or unreliable efficacy has been reported across preclinical and clinical studies. Soluble inhibitory factors, such as the secreted Wnt signaling antagonists Dickkopf‐1 (DKK1), are expressed to variable degrees in human adipose‐derived stem cells (ASCs), and may represent a targetable "molecular brake" on ASC mediated bone repair. Here, anti‐DKK1 neutralizing antibodies were observed to increase the osteogenic differentiation of human ASCs in vitro, accompanied by increased canonical Wnt signaling. Human ASCs were next engrafted into a femoral segmental bone defect in NOD‐ Scid mice, with animals subsequently treated with systemic anti‐DKK1 or isotype control during the repair process. Human ASCs alone induced significant but modest bone repair. However, systemic anti‐DKK1 induced an increase in human ASC engraftment and survival, an increase in vascular ingrowth, and ultimately improved bone repair outcomes. In summary, anti‐DKK1 can be used as a method to augment cell‐mediated bone regeneration, and could be particularly valuable in the contexts of impaired bone healing such as osteoporotic bone repair. Abstract : Systemic anti‐DKK1 treatment promotes engrafted stem cell survival, induces vascular ingrowth, and catalyzes bone matrix deposition among human adipose stem cell (ASC) treated femoral segmental bone defects. BM, bone marrow; CB, cortical bone; S, scaffold.